Characterization of solid polymer electrolytes based on poly(trimethylenecarbonate) and lithium tetrafluoroborate - Silva, Maria Manuela (2004)
The results of an investigation of a polymer electrolyte system based on the poly(trimethylene carbonate) host matrix, designated as p(TMC), with lithium tetrafluoroborate guest salt are described in this presentation. Electrolytes with lithium salt compositions with n between 3 and 80 (where n represents the number of (O=COCH2CH2CH2O) units per lithium ion) were prepared by co-dissolution of salt and polymer in anhydrous tetrahydrofuran. The homogeneous solutions obtained by this procedure were evaporated, within a preparative glovebox and under a dry argon atmosphere, to form thin films of electrolyte. The solvent-free electrolyte films produced were obtained as very flexible, transparent, completely amorphous films and were characterized by measurements of total ionic conductivity, cyclic voltammetry, differential scanning calorimetry and thermogravimetry.